If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 7g = 2 Solving 3 + 7g = 2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 7g = 2 + -3 Combine like terms: 3 + -3 = 0 0 + 7g = 2 + -3 7g = 2 + -3 Combine like terms: 2 + -3 = -1 7g = -1 Divide each side by '7'. g = -0.1428571429 Simplifying g = -0.1428571429
| 81-6x=10x+17 | | 0.4x+0.25(67-x)=22.11 | | 4y+8-3-3y=y+2 | | 4x-2=13x-101 | | x^2-4x-525=0 | | 0.4x+0.25(100-x)=31 | | 4x-20y=80 | | x^2-4x-316=209 | | -3x+3=7x+73 | | 250-4x=41x+15 | | -12-8x=48-36x | | 25x^4-401x^2+16=0 | | 57-7x=2x-24 | | 5(x+2)=5(x+8) | | -3x+3=7x+71 | | 2x+10=67-7x | | 3y+2(y-5)=1-y | | 6x-10=5x-9 | | 2(b)=14 | | (2x-5)(3x-12)=0 | | 2x+7=47-3x | | 14-7x=89-42x | | 5-2x=-x+13 | | 5x+1=3x+25 | | 10+6x=55+x | | 3x-3=13x-53 | | 5-2x=x+13 | | 51-5x=22x+15 | | 10x-15=7x+3 | | 12-10x=35-17x | | 9(2x+3)=3(x-6) | | 3(2y+1)=-3 |